Kepemimpinan Yang Menegakkan Keadilan Dan Kebenaran Pada Konteks Masa Kini (2 Samuel 8:15-18) - Clawdya Tampubolon; Eni Marlina Sihombing; Herdiana Sihombing (Jurnal Pendidikan Agama dan Teologi, 2024)
Christian leadership is leadership that needs to be done well based on biblical evidence. A Christian leader cannot be called a Christian leader if he does not live according to his foundation, which is the Bible. One of the things that makes Christian leadership good and authentic is that Christian leaders must lead by being guided by previous leaders as recorded in the Bible. David led the Israelites well in his day because he was an obedient leader and obeyed the God who sent him. The research method used in this article is critical historical interpretation by comparing current forms of Christian leadership, which are often not in line with what Christian leaders should be doing. Therefore, through this article, I hope that leaders can become leaders who are useful to the people and to God. By following this form of David-like leadership, you will be able to produce good leadership and create prosperity among God's people.